A educação de jovens e adultos e a economia solidária: perspectivas e ressignificações da educação popular - Alves, Maria Lígia Isídio (2022)
Youth and Adult Education (EJA) is conceived as an educational process that goes beyond a mechanism for repairing schooling trajectories not taken by young people, adults and the elderly in the legally expected time. Therefore, EJA is located in the field of different formative times and territories, be they school, social, economic, cultural or political. The research that gave rise to this thesis built dialogues in the field of Youth and Adult Education practices and the Soldária Economy (ECOSOL) that take place in the municipality of Lagoa de Dentro-PB. The study was developed with EJA students and teachers from the municipal network of Lagoa de Dentro/PB; producers/craftsmen/traders at the Solidarity Economy, Family Agriculture, Art and Culture Fair of Lagoa de Dentro-PB, and popular community leaders. Its main objective was to understand Youth and Adult Education in the local context, based on the links and motivations that link the dynamics of school education to the set of organizations and practices of Solidarity Economy in the territory. It was adopted as questioning the following concern: What are the implications between Youth and Adult Education and the set of Solidarity Economy organizations and initiatives in the territory through the dynamics of the students? This study is part of the theoretical-methodological approach of Popular Education as a critical epistemology, anchored in the methodological principles of Participant Research, through participant observations and semi-structured interviews. The links between EJA and Solidarity Economy move from the denunciation to the announcement. From the EJA that we have, statements of the EJA that we want emerge, through announcements of indications of how the EJA can come to be, and, in this movement, bring the school closer to the work itineraries, daily life and needs of students and workers. Popular Education, interconnected with the perspective of Solidarity Economy as multidimensional, forge spaces of resistance of the subjects of EJA in the face of the condition of oppression that, through their actions, are resignified, demonstrating expressions of creativity and exchange of knowledge that announce the construction of educational practices that assume the emancipation as a possibility of political and citizen training for the (re)configuration of EJA in public schools and uses of the territory. This formative movement clarifies that EJA subjects with mastery of knowledge from Popular Education and Solidarity Economy build a mechanism for generating work and income from the socio-productive dynamics and economic processes developed, which are not limited to immediate needs of survival, but it is configured as an integral educational dimension that values an expanded production and reproduction of life based on a solidary and inclusive perspective built by popular participation, solidarity and emancipation as a political strategy for alternative and multidimensional development. Thus, the present thesis contributes to the resignification of EJA as a process of Popular Education from the development of a pedagogy that allows relating systematized knowledge and emerging knowledge from the territorialities and daily life of the subjects and, thus, build a citizen public school.